2020
DOI: 10.1007/s10437-020-09373-y
|View full text |Cite
|
Sign up to set email alerts
|

Aerial and Spaceborne Remote Sensing in African Archaeology: A Review of Current Research and Potential Future Avenues

Abstract: Africa represents a vast region where remote sensing technologies have been largely uneven in their archaeological applications. With impending climate-related risks such as increased coastal erosion and rising sea levels, coupled with rapid urban development, gaps in our knowledge of the human history of this continent are in jeopardy of becoming permanent. Spaceborne and aerial remote sensing instruments are powerful tools for producing relatively complete records of archaeological settlement patterns and hu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 120 publications
0
12
0
Order By: Relevance
“…Mongolia also emerged as a top country in the publication of neural network literature linked to archaeology. One potential reason for this imbalance stems from funding opportunities [43,72]. When analyzing published archaeological MI literature in Web of Science, most studies were conducted by affiliates of France's Centre National de la Recherche Scientifique (CNRS), Italy's Consiglio Nazionale delle Ricerche (CNR), the Chinese Academy of Sciences, and the University of California system in the United States (Figure 4).…”
Section: Geographic Disparities Within Archaeological Machine Intellimentioning
confidence: 99%
See 2 more Smart Citations
“…Mongolia also emerged as a top country in the publication of neural network literature linked to archaeology. One potential reason for this imbalance stems from funding opportunities [43,72]. When analyzing published archaeological MI literature in Web of Science, most studies were conducted by affiliates of France's Centre National de la Recherche Scientifique (CNRS), Italy's Consiglio Nazionale delle Ricerche (CNR), the Chinese Academy of Sciences, and the University of California system in the United States (Figure 4).…”
Section: Geographic Disparities Within Archaeological Machine Intellimentioning
confidence: 99%
“…In the developing world, where funding is limited compared to places like Europe, foreign scholars with monetary support tend to be responsible for the development of MI methods (when they exist) [43]. A survey conducted by ref [72] found that most R&D expenditures in Africa are covered by international grants outside of the African continent.…”
Section: Geographic Disparities Within Archaeological Machine Intellimentioning
confidence: 99%
See 1 more Smart Citation
“…PlanetScope imagery offers exciting possibilities for regular monitoring of sites, but has not yet attracted significant attention in the archaeological remote sensing literature; few projects have adopted it. For example, Davis and Douglass' recent review [7] neglects to mention it. It is not completely open-source, however a free license for a limited quantity of data per month is available for many types of stakeholder.…”
Section: Datasetsmentioning
confidence: 99%
“…In this paper, we demonstrate the results of applying a bespoke change detection workflow using Google Earth Engine to two case studies ( Figure 1); the Aswan and Kom-Ombo area in Egypt (collaborating with the Aswan-Kom Ombo Archaeological Project, AKAP, directed by Maria Gatto and Given that it allows rapid recording via a bird's eye perspective, remote sensing has been an important part of archaeology in North Africa for several decades, although modern high-resolution imagery is underutilised [6]. Davis and Douglass' recent review paper [7] (p. 11 Figure 1) describes this trajectory in detail and maps the geographical range of these studies. Tapete and Cigna's review shows the recent expansion of scientific literature discussing satellite imagery for looting detection [8].…”
Section: Introductionmentioning
confidence: 99%